PENGARUH LAMA SIMPAN EKSTRAK FUNGISIDA NABATI TERHADAP EFEKTIVITASNYA PADA CENDAWAN Drechsleraoryzae PATOGEN TANAMAN PADI (The Long Effect Save Botanical Extract to Efectivenes of Drechslera oryzae Pathogen on Rice) - yani, Pandri; pesi, H., Panu; priati, L., Su; A., A., Djaya (AGRIPEAT, 2017)
ABSTRACTThe objectives of this study were to analyze incubation period of biofungicide extract to controlDrechslera oryzae pathogen on rice in vitro. The research was conducted from August toNovember , 2016 at Departement Budidaya Pertanian laboratory, used randomized completelydesign, with 35 treatment and 3 replications. Eight of biofungiside were used in this study,there are lerak fruits, siam weed leaves, taya leaves, gelinggang leaves, meniran, roots andtegari stem, galam leaves and 5 incubation periode (0, 1, 2, 3, 4 week) . The results showed that0â4 week incubation periode of lerak fruits extract had clear effective to inhibit D. oryzaecolony.Key words:Biofungicide extract, Drechslera oryzae, incubation period.